Trust-based multi-level secure routing for authentication and authorisation in WMN. (5th November 2021) - Sharma, Parveen Kumar; Mahajan, Rajiv; ,
Wireless-mesh-networking (WMN) is a developing technology in which users may have different authorisation-levels by not accessing information for which their authorisation level is lower. Hence, we propose to design a trust-based multi-level secure routing protocol (RP) for authentication and authorisation (TMSR-AA) in WMN. The path trust value (PTV) is calculated along the route from these trust tables. Hence, the multi-level security (MLS) is used to transmit the data by categorising into different security levels (SLs). The packets transmitted in the network are assigned an SL based on the type of data, a mesh-router with a specific SL to send packets only at the same-level or at lower-level during transmission. The performance of the 'TMSR-AA-WMN' protocol upholds a trust table with its neighbouring nodes and routing protocol for authentication and authorisation. The 'TMSR-AA-WMN' is compared with 'ESR' protocol in terms of packet-delivery-ratio, packet-drop, delay, computational over-head, communication over-head and detection-accuracy.